The Influence of Exchange Rate on Inflation in Indonesia (2003 – 2012) - Setyoparwati, Indirasari Cynthia; Ismail, Munawar (Fakultas Ekonomi dan Bisnis Universitas Brawijaya, 2016)
This study examines the effect of the exchange rate on inflation in Indonesia by using monthly data of the period of 2003-2012. In addition to entering the exchange rate as the main independent variable, this study also includes SBI rate and the money supply as a control variable. By applying multiple regression, this study confirmed that the exchange rate and interest rate SBI significantly affected inflation. Meanwhile, the money supply was not a significant variable influencing inflation.Â Keywords: Inflation, SBI Rate, Money Supply, Exchange Rate